Productivity of Robusta Coffee Farming in Rindu Hati Village Gumay Ulu District, Lahat Regency, South Sumatra: Produktivitas Usahatani Kopi Robusta di Desa Rindu Hati Kecamatan Gumay Ulu Kabupaten Lahat Sumatera Selatan - Uwi’ah, Mutata; Amri, Syaiful; Sari, Maya (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2024)
Coffee is an important agricultural commodity in Indonesia, which has a significant contribution to the economy and people's livelihoods, including in Lahat Regency. This research aims to identify the productivity of robusta coffee in Rindu Hati Village, Gumay Ulu District, Lahat Regency and determine the factors that influence coffee productivity in Lahat Regency. The research method uses primary and secondary, the sumpling method uses a simple random sampling method with a sample size of 32 respondents. The data analysis method uses descriptive methods and is presented with the help of tables. The results of this research are that Rindu Hati Village has robusta coffee productivity with a value of 0.9 tons/ha, as well as the factors that cause productivity, namely internal and external factors. Keywords: Harvest Area, Production, and Productivity